Yogi Bear [videorecording (DVD)] - Debney, John (Warner Bros. Entertainment, 2011)
"Everyone's favorite pic-a-nic basket-stealing bear brings his meal-mooching ways to movies in this live-action/CG-animated adventure ... Jellystone has been losing business, so conniving Mayor Brown has decided to shut it down and sell the land. Faced with the loss of his home, Yogi must prove he really is 'smarter than the average bear' as he and Boo Boo join forces with Ranger Smith to find a way to save the park from closing forever"--Container.